Combination of everolimus and low-dose tacrolimus controls histological liver allograft injury as sufficiently as high-dose tacrolimus - Bosselmann, Emily A.; Dranicki, Fabian; Campos-Murguia, Alejandro; Hartleben, Björn; Wedemeyer, Heiner; Jaeckel, Elmar; Taubert, Richard (Frontiers in Transplantation, 2023)
The combination of everolimus (EVR) and low-dose tacrolimus (lowTAC) prevents T cell-mediated rejection of liver grafts as sufficiently as high-dose tacrolimus (highTAC) and mycophenolate , but is associated with a preserved kidney function within the first years after orthotopic liver transplantation (OLT). However, none of the available studies assessed the histological pattern of graft injury or fibrosis in surveillance biopsies (svLbx). All svLbx taken under at least one month of stable immunosuppression with either EVR (aim 3-8 ng/ml) combined with lowTAC (aim 3-5 ng/ml) or highTAC (aim 5-8 ng/ml) combined with mycophenolate (500-1500 mg/day) within the first three to four years after OLT at our center were included. Patients who were switched to EVR because of insufficient control of alloreactivity were excluded. Reasons for switches to EVR were mainly malignancies before or after OLT, or chronic kidney injury. We were able to include 20 svLbx with EVR/lowTAC and 49 with highTAC/mycophenolate. Both groups had similar liver enzymes and similar kidney function. The EVR/lowTAC group exhibited lower TAC trough levels at svLbx (4.4 vs. 6.6 ng/ml; p<.001) in comparison to highTAC/mycophenolate. Histological graft injury quantified by the rejection activity index and hepatitis activity index (Ishak), as well as fibrosis were not significantly different between the EVR/lowTAC and highTAC/mycophenolate groups. Likewise, subclinical TCMR, histological criteria justifying immunosuppression minimization and steatosis had equal prevalence in both regimens. Immunosuppression was adjusted according to the svLbx findings. Immunosuppression regimens had similarly low rates of rejection after immunosuppression reduction, when relevant graft injury was absent in the biopsy. In conclusion, EVR/lowTAC seems to control alloreactivity and histological graft injury as sufficiently as highTAC/mycophenolate within the first 3-4 years after OLT.